Preparation method of anti-cracking modified EVA cable material

By mixing antibacterial modified HDPE, EVA, and UV-resistant modified magnesium hydroxide and preparing crack-resistant modified EVA cable material, the problem of existing EVA cables being prone to bacterial growth and poor UV resistance in humid environments is solved, and multiple performance improvements of the material are achieved.

CN119798830AActive Publication Date: 2025-04-11ANHUI YANGZI IND CO LTD

Patent Information

Application Number
CN202510049922.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-11
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Existing EVA cables are prone to bacterial growth in humid or wet environments, have short service life and poor UV resistance.

Method used

By uniformly mixing materials such as antibacterial modified high-density polyethylene (HDPE), ethylene-vinyl acetate copolymer (EVA), UV-resistant modified magnesium hydroxide, etc., and preparing crack-resistant modified EVA cable material by melting. The material contains quaternary ammonium salt groups and azo groups, which can improve antibacterial and ultraviolet resistance.

Benefits of technology

The prepared crack-resistant modified EVA cable material not only has good antibacterial properties and ultraviolet resistance, but also improves the crack-resistant and flame-retardant properties of the material and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798830A_ABST
    Figure CN119798830A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses a preparation method of an anti-cracking modified EVA cable material.The preparation method comprises the steps that maleic anhydride, N, N-bis (2-aminoethyl) methylamine, benzyl chloride and HDPE serve as raw materials, antibacterial modified HDPE is prepared through a dehydration ring-closing one-step method and a solution method, and the anti-cracking modified EVA cable material is obtained; the preparation method comprises the following steps: taking antibacterial modified HDPE as a raw material, then taking benzotriazole, bis (2-chloroethyl) amine, 3-chloropropyltrimethoxysilane and magnesium hydroxide as raw materials, performing substitution reaction and polymerization reaction to prepare anti-ultraviolet modified magnesium hydroxide, and finally taking antibacterial modified HDPE, EVA, the anti-ultraviolet modified magnesium hydroxide, red phosphorus and the like as raw materials, and performing melting method to prepare the anti-cracking modified EVA cable material. The anti-cracking modified EVA cable material prepared by the preparation method disclosed by the invention has relatively good anti-cracking performance, antibacterial performance, flame-retardant performance and anti-ultraviolet performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a method for preparing crack-resistant modified EVA cable material. Background Art

[0002] EVA is a commonly used thermoplastic polymer material, which is copolymerized by non-polar ethylene monomer and highly polar vinyl acetate monomer (VA) in a certain ratio. Due to the introduction of vinyl acetate monomer in the molecular chain, the flexibility, impact resistance, filler compatibility and heat sealing performance are improved. It is widely used in functional films, packaging materials, electrical insulation, cable industry, hot melt adhesives and biomedical equipment. There are only three elements C, H and O in the EVA molecular structure, which makes EVA very flammable, with a large amount of heat release and severe melting when burning. At the same time, EVA has good insulation and excellent physical and mechanical properties.

[0003] For example, the patent with the authorization announcement number CN116396551A discloses a polyethylene composition and its preparation method and application. The invention is based on high-density polyethylene, ethylene-vinyl acetate copolymer EVA, EVA-g-NBR, flaky aluminum hydroxide, montmorillonite, silane coupling agent, initiator, and antioxidant. The raw materials and formula combination selected in this patent not only have good mechanical and flame retardant properties, but also have excellent oil resistance, which is very suitable for use in cables that are in long-term contact with alkane oil substances. However, the cables prepared by this invention are not suitable for humid or moist environments. In such environments, bacteria are easily bred, shortening the service life, and the anti-ultraviolet performance is poor. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a crack-resistant modified EVA cable material. The prepared modified EVA cable material has good antibacterial and anti-ultraviolet properties.

[0006] (II) Technical solution

[0007] A method for preparing a crack-resistant modified EVA cable material, the preparation method being as follows:

[0008] The antibacterial modified high-density polyethylene (HDPE) and ethylene-vinyl acetate copolymer (EVA) are uniformly mixed to obtain a premix, half of the premix is ​​taken, added to an open mill, and the temperature is raised to 90-110°C, and the other half of the premix, anti-ultraviolet modified magnesium hydroxide, red phosphorus, superdispersant polyvinyl pyrrolidone, and antioxidant quercetin are evenly mixed, and then added to the open mill, and the mixture is opened for 8-12 minutes, stirred and mixed for 3-7 minutes, and then a vulcanizing agent diisopropyl peroxide (DCP) and a vulcanization accelerator triallyl isocyanurate (TAIC) are added, and the mixture is opened for 3-7 minutes to obtain a rubber compound, and the rubber compound is placed in a flat vulcanizer, the temperature is raised to 160-180°C, the pressure is 3-7MPa, the vulcanization is carried out for 15-25 minutes, and then the mixture is cooled for 3-7 minutes to obtain a crack-resistant modified EVA cable material.

[0009] Preferably, the preparation method of the antibacterial modified HDPE is as follows:

[0010] S1, add maleic anhydride to isopropanol solution, heat to 15-25°C, add N,N-bis(2-aminoethyl)methylamine dropwise thereto, keep warm for 0.5-1.5h, then add acetic anhydride and sodium acetate, heat to 25-30°C, react for 2-3h, filter, wash with deionized water, and dry at 40-50°C to obtain intermediate 1;

[0011] S2, adding benzyl chloride and intermediate 1 into N,N-dimethylformamide (DMF) solvent, then adding ethyl acetate catalyst, heating to 50-70°C, stirring for reaction for 5-7h, cooling to room temperature, precipitating with ether, filtering, and obtaining quaternary ammonium salt-modified maleic anhydride;

[0012] S3. Add HDPE to xylene solution, heat to 130-140°C, stir until completely dissolved, then add quaternary ammonium salt modified maleic anhydride and benzoyl peroxide (BPO) initiator, react for 2-4h, cool to 20-30°C, filter, wash with acetone, and dry to obtain modified maleic anhydride grafted polyethylene.

[0013] Preferably, the preparation method of the UV-resistant modified magnesium hydroxide is as follows:

[0014] SS1, add benzotriazole to ethanol solvent, stir to dissolve, add sodium hydroxide, stir, heat to 45-65°C, add bis(2-chloroethyl)amine, stir, continue to heat to 75-85°C, react for 22-26h, distill under reduced pressure, wash with hot deionized water, separate layers, dry with calcium chloride to obtain intermediate 2;

[0015] SS2, add intermediate 2 to ether solvent, introduce nitrogen, add 3-chloropropyltrimethoxysilane dropwise for 1-2h, raise the temperature to 30-40°C, react for 6-8h, let stand for 12-16h, filter, wash with anhydrous ether, and distill at low pressure to obtain benzotriazole modified silane coupling agent;

[0016] SS3. Dry the magnesium hydroxide in a drying oven, heat it to 100-120°C, dry it for 8-12 hours, cool it to room temperature, add it to deionized water, stir it for 8-12 minutes, add benzotriazole modified silane coupling agent ethanol solution, heat it to 30-50°C, stir and react for 20-40 minutes. After the reaction is completed, cool it to room temperature, filter, wash, dry, grind, and sieve to obtain modified magnesium hydroxide.

[0017] Preferably, the mass ratio of EVA, antibacterial modified HDPE, modified magnesium hydroxide, superdispersant polyvinyl pyrrolidone, antioxidant quercetin, DCP, and TAIC is 1:0.25-0.45:1.38-1.47:0.15-0.27:0.032-0.04:0.04-0.065:0.04-0.065.

[0018] Preferably, in step S1, the mass ratio of maleic anhydride, N,N-bis(2-aminoethyl)methylamine, acetic anhydride and sodium acetate is 1:0.55-0.60:0.12-0.14:0.006-0.007.

[0019] Preferably, in step S2, the mass ratio of intermediate 1, benzyl chloride and ethyl acetate is 1:0.36-0.55:0.1-0.2.

[0020] Preferably, in step S3, the mass ratio of HDPE, quaternary ammonium salt-modified maleic anhydride, maleic anhydride, and BPO is 1:0.02-0.1:0.02-0.1:0.005-0.03.

[0021] Preferably, in step SS1, the mass ratio of sodium hydroxide, bis(2-chloroethyl)amine and benzotriazole is 0.4-0.45:0.45-0.65:1.

[0022] Preferably, in step SS2, the mass ratio of the intermediate 2:3-chloropropyltrimethoxysilane is 1:0.12-0.14.

[0023] Preferably, in step SS3, the mass ratio of magnesium hydroxide to modified silane coupling agent is 1:0.8-1.2.

[0024] (III) Beneficial technical effects

[0025] The invention uses maleic anhydride, N, N-bis(2-aminoethyl)methylamine, benzyl chloride and HDPE as raw materials, and prepares antibacterial modified HDPE through a one-step dehydration closed-loop method and a solution method; then uses benzotriazole, bis(2-chloroethyl)amine, 3-chloropropyltrimethoxysilane and magnesium hydroxide as raw materials, and prepares anti-ultraviolet modified magnesium hydroxide through a substitution reaction and a polymerization reaction; finally, uses antibacterial modified HDPE, EVA, anti-ultraviolet modified magnesium hydroxide, red phosphorus and the like as raw materials, and prepares anti-cracking modified EVA cable material through a melting method.

[0026] The crack-resistant modified EVA cable material prepared by the present invention contains quaternary ammonium salt groups, which have positive charges and can be adsorbed on the surface of microorganisms to form micelles and gradually penetrate into the lipid layer and protein layer of the cell plasma, thereby changing the permeability of the cell membrane, causing the cell contents to extravasate, leading to the death of the microorganisms, and coagulating proteins, denaturing enzymes and structural proteins, destroying the metabolism of the microorganisms, and killing the microorganisms, thereby improving the antibacterial property of the cable.

[0027] The crack-resistant modified EVA cable material prepared by the present invention contains an azo group, which has the characteristics of photochromism and photoinduced cis-trans isomerization, and the azo group has an obvious absorption peak in the ultraviolet region (especially between 200-400nm). The reason is that the π electrons in the azo group are prone to transition under the irradiation of ultraviolet light, from a lower energy level to a higher energy level, and this transition absorbs ultraviolet light and reduces the penetration of ultraviolet light, thereby achieving an anti-ultraviolet effect, and introducing it into the cable material can improve the anti-ultraviolet performance of the cable material.

[0028] The anti-cracking modified EVA cable material prepared by the present invention contains HDPE, and the vinyl acetate units contained in the EVA molecular chains can interact with the molecular chains in the HDPE to form a relatively tight compatible interface, and at the same time, the increase in the cross-linking degree between HDPE and EVA makes the slippage between the molecular chains more difficult, thereby improving the anti-cracking performance of the material.

[0029] The anti-cracking modified EVA cable material prepared by the present invention contains magnesium hydroxide and red phosphorus flame retardant. Magnesium hydroxide reduces the temperature of the cable matrix through the dehydration endothermic effect of the condensed phase, dilutes the gas phase combustibles and oxygen concentration to achieve the purpose of flame retardancy and smoke elimination. At the same time, the cable contains phosphorus, nitrogen and silicon elements. The nitrogen element will decompose and produce a large amount of non-combustible gas during combustion, and the non-combustible gas can dilute the oxygen concentration around the composite material. The silicon element can migrate to the outer surface of the material during combustion, and the Si-O bond in its molecule will be converted into a Si-C bond. The generated white combustion residue and carbide form a covering layer on the surface of the composite material to prevent the combustion volatiles from escaping and prevent oxygen from contacting the matrix material, thereby improving the flame retardant performance of the cable. The phosphorus element will release a large amount of gas or high-density steam when heated or burned, which can dilute the oxygen and gaseous combustibles in the air, and reduce the surface temperature of the combustion object, causing the combustion to stop. The anti-cracking modified EVA cable material prepared by the present invention has good anti-cracking performance, antibacterial performance, flame retardant performance and anti-ultraviolet performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a preparation route for quaternary ammonium salt-modified maleic anhydride;

[0031] Figure 2 It is a preparation route for benzotriazole-modified silane coupling agent. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] (1) Add 50 g of maleic anhydride to 100 ml of isopropanol solution, heat to 15° C., add 30 g of N,N-bis(2-aminoethyl)methylamine dropwise thereto, add dropwise for 1 hour, keep warm and react for 0.5 hour, then add 7 g of acetic anhydride and 0.3 g of sodium acetate, heat to 30° C., react for 2 hours, filter, wash with deionized water, and dry at 50° C. to obtain intermediate 1.

[0035] (2) Add 18 g of benzyl chloride and 50 g of intermediate 1 to 100 ml of N,N-dimethylformamide (DMF) solvent, then add 10 g of ethyl acetate catalyst, heat to 70° C., stir to react for 5 h, cool to room temperature, precipitate with ether, and filter to obtain quaternary ammonium salt-modified maleic anhydride.

[0036] (3) Add 10 g of HDPE to 15 ml of xylene solution, heat to 140 °C, stir until completely dissolved, then add 0.2 g of quaternary ammonium salt modified maleic anhydride, 1 g of maleic anhydride and 0.1 g of benzoyl peroxide (BPO) initiator, react for 4 h, cool to 20 °C, filter, wash with acetone, and dry to obtain modified maleic anhydride grafted polyethylene.

[0037] (4) Add 10 g of benzotriazole to 50 ml of ethanol solvent, stir to dissolve, add 4.5 g of sodium hydroxide, stir, raise the temperature to 65° C., add 4 g of bis(2-chloroethyl)amine, stir, continue to raise the temperature to 80° C., react for 26 h, distill under reduced pressure, wash with hot deionized water, separate the layers, and dry with calcium chloride to obtain intermediate 2.

[0038] (5) Add 5 g of intermediate 2 to 20 ml of ether solvent, introduce nitrogen, add 0.6 g of 3-chloropropyltrimethoxysilane dropwise, add for 1.5 h, raise the temperature to 40° C., react for 6 h, let stand for 12 h, filter, wash with anhydrous ether, and distill at low pressure to obtain a benzotriazole-modified silane coupling agent.

[0039] (6) 1 g of magnesium hydroxide was placed in a drying oven and dried, heated to 110° C., dried for 10 h, cooled to room temperature, added to deionized water, stirred for 10 min, and then 1.3 g of benzotriazole-modified silane coupling agent ethanol solution was added, heated to 40° C., stirred for 30 min, and after the reaction was completed, cooled to room temperature, filtered, washed, dried, ground, and sieved to obtain modified magnesium hydroxide.

[0040] (7) 4.5 g of antibacterial modified high-density polyethylene (HDPE) and 10 g of ethylene-vinyl acetate copolymer (EVA) were uniformly mixed to obtain a premix. Half of the premix was taken and added to an open mill and heated to 90°C. The other half of the premix, 14.5 g of anti-ultraviolet modified magnesium hydroxide, 1 g of red phosphorus, 1.5 g of superdispersant polyvinyl pyrrolidone, and 0.32 g of antioxidant quercetin were mixed uniformly and added to an open mill. The mixture was then mixed for 12 min and stirred for 5 min. Then, 0.4 g of vulcanizing agent diisopropyl peroxide (DCP) and 0.5 g of vulcanization accelerator triallyl isocyanurate (TAIC) were added and mixed for another 7 min. The mixed rubber was placed in a flat vulcanizer, heated to 160°C, pressure 3 MPa, vulcanized for 20 min, and cooled for 7 min to obtain anti-cracking modified EVA cable material.

[0041] Example 2

[0042] (1) Add 50 g of maleic anhydride to 100 ml of isopropanol solution, heat to 22° C., add 28 g of N,N-bis(2-aminoethyl)methylamine dropwise thereto, add for 0.75 h, keep warm for 0.5 h, then add 6 g of acetic anhydride and 0.31 g of sodium acetate, heat to 28° C., react for 2.5 h, filter, wash with deionized water, and dry at 45° C. to obtain intermediate 1.

[0043] (2) Add 20 g of benzyl chloride and 50 g of intermediate 1 to 100 ml of DMF solvent, then add 7.5 g of ethyl acetate catalyst, heat to 60° C., stir to react for 5.7 h, cool to room temperature, precipitate with ether, and filter to obtain quaternary ammonium salt-modified maleic anhydride.

[0044] (3) Add 10 g of HDPE to 50 ml of xylene solution, heat to 132°C, stir until completely dissolved, then add 0.22 g of quaternary ammonium salt modified maleic anhydride, 0.5 g of maleic anhydride and 0.05 g of BPO initiator, react for 2.4 h, cool to 25°C, filter, wash with acetone, and dry to obtain modified maleic anhydride grafted polyethylene.

[0045] (4) Add 10 g of benzotriazole to 50 ml of ethanol solvent, stir to dissolve, add 4.3 g of sodium hydroxide, stir, raise the temperature to 48°C, add 4.8 g of bis(2-chloroethyl)amine, stir, continue to raise the temperature to 78°C, react for 24 h, distill under reduced pressure, wash with hot deionized water, separate the layers, and dry with calcium chloride to obtain intermediate 2.

[0046] (5) Add 10 g of intermediate 2 to 20 ml of ether solvent, introduce nitrogen, add 1.3 g of 3-chloropropyltrimethoxysilane dropwise, add for 1.2 h, raise the temperature to 35° C., react for 6.8 h, let stand for 16 h, filter, wash with anhydrous ether, and distill at low pressure to obtain benzotriazole-modified silane coupling agent.

[0047] (6) 10 g of magnesium hydroxide was placed in a drying oven and dried, heated to 105° C., dried for 9 h, cooled to room temperature, added to deionized water, stirred for 10 min, and then added with 12 g of an ethanol solution of a benzotriazole-modified silane coupling agent, heated to 35° C., stirred for 24 min, and after the reaction was completed, cooled to room temperature, filtered, washed, dried, ground, and sieved to obtain modified magnesium hydroxide.

[0048] (7) 3.5 g of antibacterial modified HDPE and 10 g of EVA were uniformly mixed to obtain a premix. Half of the premix was taken and added to an open mill and heated to 95° C. The other half of the premix, 13.5 g of anti-ultraviolet modified magnesium hydroxide, 1 g of red phosphorus, 0.35 g of a superdispersant, and 0.5 g of an antioxidant were mixed uniformly and added to an open mill. The premix was then mixed for 9 min and stirred for 5 min. 0.6 g of a vulcanizing agent DCP and 0.4 g of a vulcanization accelerator TAIC were then added and mixed for another 6 min. The mixed rubber was placed in a flat vulcanizer, heated to 165° C., pressure 4 MPa, vulcanized for 18 min, and cooled for 6 min to obtain a crack-resistant modified EVA cable material.

[0049] Example 3

[0050] (1) Add 30 g of maleic anhydride to 100 ml of isopropanol solution, heat to 20°C, add 17.4 g of N,N-bis(2-aminoethyl)methylamine dropwise thereto, add for 0.75 h, keep warm for 1.2 h, then add 3.9 g of acetic anhydride and 0.195 g of sodium acetate, heat to 28°C, react for 2.8 h, filter, wash with deionized water, and dry at 44°C to obtain intermediate 1.

[0051] (2) 16.5 g of benzyl chloride and 30 g of intermediate 1 were added to 100 ml of DMF solvent, and 4.5 g of ethyl acetate catalyst was added. The temperature was raised to 55° C. and stirred for reaction for 5.7 h. The mixture was cooled to room temperature, precipitated with ether, and filtered to obtain quaternary ammonium salt-modified maleic anhydride.

[0052] (3) Add 10 g of HDPE to 50 ml of xylene solution, heat to 134°C, stir until completely dissolved, then add 0.25 g of quaternary ammonium salt modified maleic anhydride, 0.3 g of maleic anhydride and 0.2 g of BPO initiator, react for 2.6 h, cool to 30°C, filter, wash with acetone, and dry to obtain modified maleic anhydride grafted polyethylene.

[0053] (4) Add 10 g of benzotriazole to 50 ml of ethanol solvent, stir to dissolve, add 4.2 g of sodium hydroxide, stir, raise the temperature to 50° C., add 6.2 g of bis(2-chloroethyl)amine, stir, continue to raise the temperature to 80° C., react for 25 h, distill under reduced pressure, wash with hot deionized water, separate the layers, and dry with calcium chloride to obtain intermediate 2.

[0054] (5) Add 10 g of intermediate 2 to 50 ml of ether solvent, introduce nitrogen, add 1.2 g of 3-chloropropyltrimethoxysilane dropwise for 1 hour, raise the temperature to 38°C, react for 7 hours, let stand for 14 hours, filter, wash with anhydrous ether, and distill at low pressure to obtain benzotriazole modified silane coupling agent.

[0055] (6) 10 g of magnesium hydroxide was placed in a drying oven and dried, heated to 120° C., dried for 8 h, cooled to room temperature, added to deionized water, stirred for 12 min, and then 13 g of benzotriazole-modified silane coupling agent ethanol solution was added, heated to 40° C., stirred for 40 min, and after the reaction was completed, cooled to room temperature, filtered, washed, dried, ground, and sieved to obtain modified magnesium hydroxide.

[0056] (7) 3 g of antibacterial modified HDPE and 10 g of EVA were uniformly mixed to obtain a premix. Half of the premix was taken and added to an open mill and heated to 110° C. The other half of the premix, 12.5 g of anti-ultraviolet modified magnesium hydroxide, 1 g of red phosphorus, 2.5 g of a superdispersant, and 0.38 g of an antioxidant were mixed uniformly and added to an open mill for 9 min. The mixture was stirred and mixed for 3 min. 0.65 g of a vulcanizing agent DCP and 0.6 g of a vulcanizing accelerator TAIC were added and the mixture was further refined for 3.5 min. The mixed rubber was placed in a flat vulcanizer, heated to 178° C., pressure 6.5 MPa, vulcanized for 23 min, and cooled for 4 min to obtain a crack-resistant modified EVA cable material.

[0057] Example 4

[0058] (1) 30 g of maleic anhydride was added to 100 ml of isopropanol solution, the temperature was raised to 25° C., 18 g of N,N-bis(2-aminoethyl)methylamine was added dropwise thereto, and the temperature was kept to react for 1.5 h. Then 3.9 g of acetic anhydride and 0.63 g of sodium acetate were added, the temperature was raised to 30° C., the reaction was carried out for 2 h, the solution was filtered, washed with deionized water, and dried at 50° C. to obtain intermediate 1.

[0059] (2) 10.8 g of benzyl chloride and 30 g of intermediate 1 were added to 100 ml of DMF solvent, and then 3 g of ethyl acetate catalyst was added. The temperature was raised to 70° C. and stirred for reaction for 7 h. The mixture was cooled to room temperature, precipitated with ether, and filtered to obtain quaternary ammonium salt-modified maleic anhydride.

[0060] (3) Add 10 g of HDPE to 50 ml of xylene solution, heat to 140°C, stir until completely dissolved, then add 1 g of quaternary ammonium salt modified maleic anhydride, 1 g of maleic anhydride and 0.3 g of BPO initiator, react for 4 h, cool to 30°C, filter, wash with acetone, and dry to obtain modified maleic anhydride grafted polyethylene.

[0061] (4) Add 10 g of benzotriazole to 50 ml of ethanol solvent, stir to dissolve, add 4 g of sodium hydroxide, stir, raise the temperature to 65° C., add 6.5 g of bis(2-chloroethyl)amine, stir, continue to raise the temperature to 85° C., react for 22 h, distill under reduced pressure, wash with hot deionized water, separate the layers, and dry with calcium chloride to obtain intermediate 2.

[0062] (5) Add 10 g of intermediate 2 to 50 ml of ether solvent, introduce nitrogen, add 1.4 g of 3-chloropropyltrimethoxysilane dropwise for 2 h, raise the temperature to 40 °C, react for 6 h, let stand for 16 h, filter, wash with anhydrous ether, and distill at low pressure to obtain benzotriazole modified silane coupling agent.

[0063] (6) 10 g of magnesium hydroxide was placed in a drying oven and dried, heated to 115° C., dried for 11 h, cooled to room temperature, added to deionized water, stirred for 11 min, and then 8 g of benzotriazole-modified silane coupling agent ethanol solution was added, heated to 45° C., stirred for 35 min, and after the reaction was completed, cooled to room temperature, filtered, washed, dried, ground, and sieved to obtain modified magnesium hydroxide.

[0064] (7) 2.5 g of antibacterial modified HDPE and 10 g of EVA were uniformly mixed to obtain a premix. Half of the premix was taken and added to an open mill and heated to 110° C. The other half of the premix, 13 g of anti-ultraviolet modified magnesium hydroxide, 1 g of red phosphorus, 2.7 g of a superdispersant, and 0.4 g of an antioxidant were mixed uniformly and added to an open mill for 8 min. The mixture was stirred and mixed for 5 min. 0.5 g of a vulcanizing agent DCP and 0.65 g of a vulcanizing accelerator TAIC were added and the mixture was further refined for 5 min. The mixed rubber was placed in a flat vulcanizer, heated to 180° C., pressure 7 MPa, vulcanized for 25 min, and then cooled for 4.5 min to obtain a crack-resistant modified EVA cable material.

[0065] Comparative Example 1

[0066] The difference between this comparative example and Example 1 is that no antimicrobial modified HDPE is added in Comparative Example 1.

[0067] Comparative Example 2

[0068] The difference between this comparative example and Example 1 is that no anti-ultraviolet modified magnesium hydroxide is added in Comparative Example 2.

[0069] Comparative Example 3

[0070] The difference between this comparative example and Example 1 is that the antibacterial modified HDPE added in Comparative Example 3 is replaced by HDPE, and the anti-ultraviolet modified magnesium hydroxide added is replaced by magnesium hydroxide.

[0071] Cracking resistance test

[0072] Take the cable materials of Examples 1-4 and Comparative Examples 1-3, first wind them with a load of 5 kg, place them at room temperature for 1 hour, observe whether they crack, then increase the load to 7 kg, and observe whether they crack under the same test conditions. If there is no crack, the crack resistance is good.

[0073] Tensile strength and elongation at break tests

[0074] The cable materials of Examples 1-4 and Comparative Examples 1-3 were tested with an electronic tensile testing machine KD-1 (0-1 KN). The tensile strength and elongation at break were in accordance with the GB / T 1040.1--2006 standard.

[0075] Table 1: Performance test results of various embodiments and comparative examples

[0076]

[0077]

[0078] As can be seen from Table 1, no cracks appeared on the surfaces of Examples 1-4 and Comparative Examples 2-3 after the anti-cracking test, so their anti-cracking performance is good. The tensile strengths of Examples 1-4 and Comparative Examples 2-3 are relatively close, and are significantly higher than Comparative Example 1. Although the elongation at break of Comparative Example 1 is significantly higher than that of other samples, its low tensile strength and cracking phenomenon indicate that the material has insufficient toughness and cannot effectively disperse external stress, so it is easy to crack. The reason is that Examples 1-4 and Comparative Examples 2-3 all contain HDPE, and the molecular structures of HDPE and EVA are compatible. HDPE is a linear polymer with a high degree of crystallinity. The vinyl acetate units contained in the EVA molecular chains can interact with the molecular chains in HDPE to form a relatively tight compatible interface. At the same time, the increase in the degree of crosslinking between HDPE and EVA makes it more difficult to slip between the molecular chains, thereby improving the anti-cracking performance of the material.

[0079] Flame retardancy test

[0080] The cable materials of Examples 1-4 and Comparative Examples 1-3 were tested for oxygen index using an oxygen index tester (YG813 model) in accordance with GB / T2406.2--2009 standard.

[0081] Table 2: Flame retardant performance test results of various embodiments and comparative examples

[0082]

[0083]

[0084] The higher the oxygen index, the better the flame retardancy of the material. It can be seen from Table 2 that the oxygen indexes of Examples 1-4, Comparative Examples 1 and 3 are relatively high. The reason is that Examples 1-4, Comparative Examples 1 and 3 contain magnesium hydroxide, which reduces the temperature of the cable matrix through the dehydration and heat absorption of the condensed phase, dilutes the gas phase combustibles and oxygen concentration to achieve the purpose of flame retardancy and smoke suppression.

[0085] Compared with Comparative Example 3, Example 1 has a higher oxygen index because Example 1 contains more nitrogen and silicon elements. The nitrogen element will decompose to produce a large amount of non-combustible gas during combustion, and the non-combustible gas can dilute the concentration of oxygen around the composite material. The silicon element can migrate to the outer surface of the material during combustion, and the Si-O bonds in its molecules will be converted into Si-C bonds. The generated white combustion residues and carbides form a covering layer on the surface of the composite material, preventing the combustion volatiles from escaping and preventing oxygen from contacting the matrix material, thereby improving the flame retardant properties of the cable.

[0086] Antimicrobial testing

[0087] (1) The cable materials of Examples 1-4 and Comparative Examples 1-3 were cut into 1 mm×1 mm×12 mm blocks, sterilized with 0.1 MPa steam for 40-50 min, dried, and set aside.

[0088] (2) Add 0.03 mol / L phosphate buffer (PBS) to the flask, sterilize with 0.1 MPa steam for 15-25 min, cool to room temperature, then use a pipette to transfer the E. coli solution to the flask, and prepare the bacterial suspension in PBS to a concentration of about 1×10 4 cfu / ml.

[0089] (3) The flask was fixed on a shaking table, heated to 30°C, shaken at 220 r / min for 2 min, and 1.0 ml was taken out and diluted appropriately to 10 with PBS. 2 .

[0090] (4) Place the samples of Example 1-4 and Comparative Example 1-3 in the above flasks respectively, heat to 30°C, shake at 220 r / min for 24 h, and take 1.0 ml of the samples and dilute to 10% with PBS. 2 , as sample liquid.

[0091] (5) 1.0 ml of the sample solution before and after shaking was taken respectively, and inoculated into a plate by the agar pouring method. The plate was placed in a 37°C incubator for 24 h, and the live bacteria were counted. The bacterial concentration in the flask before and after shaking was measured, and the antibacterial rate was calculated.

[0092] R(%)={(BA) / B}×100

[0093] Where: R is the antibacterial rate, %; A is the colony count after the sample is shaken for 24 hours, cfu / ml; B is the colony count before the sample is shaken, cfu / ml.

[0094] Table 3: Antibacterial test results of various embodiments and comparative examples

[0095] Before shaking (cfu / ml) After shaking (cfu / ml) Antibacterial rate (%) Example 1 <![CDATA[9.10×10 3 ]]> <![CDATA[1.0×10 1 ]]> 99.99 Example 2 <![CDATA[9.25×10 3 ]]> <![CDATA[7.0×10 2 ]]> 92.42 Example 3 <![CDATA[8.94×10 3 ]]> <![CDATA[1.5×10 3 ]]> 83.22 Example 4 <![CDATA[8.83×10 3 ]]> <![CDATA[8.0×10 2 ]]> 86.80 Comparative Example 1 <![CDATA[9.46×10 3 ]]> <![CDATA[1.29×10 4 ]]> - Comparative Example 2 <![CDATA[9.83×10 3 ]]> <![CDATA[2.0×10 1 ]]> 99.80 Comparative Example 3 <![CDATA[9.58×10 3 ]]> <![CDATA[1.43×10 4 ]]> -

[0096] As can be seen from Table 3, the antibacterial rates of Examples 1-4 and Comparative Example 2 both reached 80%, and the bacterial concentration was significantly reduced. Therefore, Examples 1-4 and Comparative Example 2 had significant antibacterial effects. The reason is that Examples 1-4 and Comparative Example 2 contain quaternary ammonium groups, which have positive charges and can be adsorbed on the surface of microorganisms to form micelles, and gradually penetrate into the lipid layer and protein layer of the cytoplasm, thereby changing the permeability of the cell membrane, causing the cell contents to extravasate, leading to the death of the microorganisms, and at the same time coagulating proteins, denaturing enzymes and structural proteins, destroying the metabolism of microorganisms, and killing the microorganisms, thereby improving the antibacterial properties of the cable.

[0097] UV resistance detection

[0098] (1) Take the cables of Example 1-4 and Comparative Example 1-3, place them in a fluorescent 313 lamp, and set a heated water reservoir in the UV2000 box, irradiate them at a temperature of 60° C. for 4 hours, and then place them at 50° C. for condensation for 4 hours.

[0099] (2) The cable materials of Examples 1-4 and Comparative Examples 1-3 were tested for tensile strength and elongation at break using an electronic tensile testing machine KD-1 (0-1 KN) in accordance with GB / T 1040.1--2006.

[0100] Table 4: Anti-ultraviolet aging test results of various embodiments and comparative examples

[0101]

[0102] As can be seen from Table 4, the tensile strength of Examples 1-4 and Comparative Example 1 generally decreases to a certain extent, with an average decrease of about 1.0 MPa, while the tensile strength of Comparative Examples 2-3 decreases slightly more, with an average decrease of about 2.45 MPa. It can be seen that the anti-ultraviolet performance of Examples 1-4 and Comparative Example 1 is better than that of Comparative Examples 2-3. The reason is that both Examples 1-4 and Comparative Example 1 contain azo groups, which have the characteristics of photochromism and photoinduced cis-trans isomerization, and the azo groups have obvious absorption peaks in the ultraviolet region (especially between 200-400 nm). The reason is that the π electrons in the azo groups are prone to transition under the irradiation of ultraviolet light, from a lower energy level to a higher energy level. This transition absorbs ultraviolet light and reduces the penetration of ultraviolet light, thereby achieving an anti-ultraviolet effect.

Claims

1. A method for preparing a crack-resistant modified EVA cable material, characterized in that: The preparation method is as follows: The antibacterial modified high-density polyethylene (HDPE) and ethylene-vinyl acetate copolymer (EVA) are uniformly mixed to obtain a premix, half of the premix is ​​taken, added to an open mill, and the temperature is raised to 90-110°C, and the other half of the premix, anti-ultraviolet modified magnesium hydroxide, red phosphorus, superdispersant polyvinyl pyrrolidone, and antioxidant quercetin are evenly mixed, and then added to the open mill, and the mixture is opened for 8-12 minutes, stirred and mixed for 3-7 minutes, and then a vulcanizing agent diisopropyl peroxide (DCP) and a vulcanization accelerator triallyl isocyanurate (TAIC) are added, and the mixture is opened for 3-7 minutes to obtain a rubber compound, and the rubber compound is placed in a flat vulcanizer, the temperature is raised to 160-180°C, the pressure is 3-7MPa, the vulcanization is carried out for 15-25 minutes, and then the mixture is cooled for 3-7 minutes to obtain a crack-resistant modified EVA cable material.

2. The method for preparing the crack-resistant modified EVA cable material according to claim 1, characterized in that: The preparation method of the antibacterial modified HDPE is as follows: S1. Add maleic anhydride to isopropanol solution, add N,N-bis(2-aminoethyl)methylamine dropwise thereto at 15-25°C, keep warm for 0.5-1.5h, then add acetic anhydride and sodium acetate, raise the temperature to 25-30°C, react for 2-3h, filter, wash with deionized water, and dry at 40-50°C to obtain intermediate 1; S2, adding benzyl chloride and intermediate 1 into N,N-dimethylformamide (DMF) solvent, then adding ethyl acetate catalyst, heating to 50-70°C, stirring for reaction for 5-7h, cooling to room temperature, precipitating with ether, filtering, and obtaining quaternary ammonium salt-modified maleic anhydride; S3. Add HDPE to xylene solution, heat to 130-140°C, stir until completely dissolved, then add quaternary ammonium salt modified maleic anhydride, maleic anhydride and benzoyl peroxide (BPO) initiator, react for 2-4h, cool to 20-30°C, filter, wash with acetone, and dry to obtain modified maleic anhydride grafted polyethylene.

3. The method for preparing the crack-resistant modified EVA cable material according to claim 1, characterized in that: The preparation method of the anti-ultraviolet modified magnesium hydroxide is as follows: SS1, add benzotriazole to ethanol solvent, stir to dissolve, add sodium hydroxide, stir, heat to 45-65°C, add bis(2-chloroethyl)amine, stir, continue to heat to 75-85°C, react for 22-26h, distill under reduced pressure, wash with hot deionized water, dry with calcium chloride to obtain intermediate 2; SS2, add intermediate 2 to ether solvent, introduce nitrogen, add 3-chloropropyltrimethoxysilane dropwise for 1-2h, raise the temperature to 30-40°C, react for 6-8h, let stand for 12-16h, filter, wash with anhydrous ether, and distill at low pressure to obtain benzotriazole modified silane coupling agent; SS3. Dry the magnesium hydroxide in a drying oven, heat it to 100-120°C, dry it for 8-12 hours, cool it to room temperature, add it to deionized water, stir it for 8-12 minutes, add the ethanol solution of benzotriazole-modified silane coupling agent, heat it to 30-50°C, stir and react for 20-40 minutes. After the reaction is completed, cool it to room temperature, filter, wash, dry, grind, and sieve to obtain modified magnesium hydroxide.

4. The method for preparing the crack-resistant modified EVA cable material according to claim 1, characterized in that: EVA, antibacterial modified HDPE, modified magnesium hydroxide, superdispersant polyvinyl pyrrolidone, antioxidant quercetin, DCP, TAIC, and their mass ratio is 1:0.25-0.45:1.38-1.47:0.15-0.27:0.032-0.04:0.04-0.065:0.04-0.

065.

5. The method for preparing the crack-resistant modified EVA cable material according to claim 2, characterized in that: In the step S1, the mass ratio of maleic anhydride, N,N-bis(2-aminoethyl)methylamine, acetic anhydride and sodium acetate is 1:0.55-0.60:0.12-0.14:0.006-0.

007.

6. The method for preparing the crack-resistant modified EVA cable material according to claim 2, characterized in that: In the step S2, the mass ratio of intermediate 1, benzyl chloride and ethyl acetate is 1:0.36-0.55:0.1-0.

2.

7. The method for preparing the crack-resistant modified EVA cable material according to claim 2, characterized in that: In the step S3, the mass ratio of HDPE, quaternary ammonium salt modified maleic anhydride, maleic anhydride and BPO is 1:0.02-0.1:0.02-0.1:0.005-0.

03.

8. The method for preparing the crack-resistant modified EVA cable material according to claim 3, characterized in that: In the step SS1, the mass ratio of sodium hydroxide, bis(2-chloroethyl)amine and benzotriazole is 0.4-0.45:0.45-0.65:

1.

9. The method for preparing the crack-resistant modified EVA cable material according to claim 3, characterized in that: In the step SS2, the mass ratio of the intermediate 2:3-chloropropyltrimethoxysilane is 1:0.12-0.

14.

10. The method for preparing the crack-resistant modified EVA cable material according to claim 3, characterized in that: In the step SS3, the mass ratio of magnesium hydroxide to modified silane coupling agent is 1:0.8-1.2.

Citation Information

Patent Citations

  • Polyethylene composition as well as preparation method and application thereof

    CN116396551A

  • Low-smoke halogen-free and flame-retardant polyolefin cable material with high cracking resistance

    CN111635579A

  • Quaternary ammonium salt grafted antibacterial polypropylene and preparation method thereof

    CN115785342A

  • Anti-ultraviolet composite particle, anti-ultraviolet polyamide material and preparation method and application of anti-ultraviolet composite particle and anti-ultraviolet polyamide material

    CN119286063A

  • Cable

    JP2021125396A

Cited By

  • Ultralight high-strength modified chlorosulfonated polyethylene sole and preparation method thereof

    CN121086319A